2015
DOI: 10.3390/ijms160921215
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Dynamics in Demyelinating Diseases: Unraveling Complex Relationships through Computer Modeling

Abstract: Despite intense research, few treatments are available for most neurological disorders. Demyelinating diseases are no exception. This is perhaps not surprising considering the multifactorial nature of these diseases, which involve complex interactions between immune system cells, glia and neurons. In the case of multiple sclerosis, for example, there is no unanimity among researchers about the cause or even which system or cell type could be ground zero. This situation precludes the development and strategic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 118 publications
(141 reference statements)
0
21
0
Order By: Relevance
“…A fiber with a g ‐ratio around 0.6 has been theoretically shown to provide maximal speed of conducting neural signals in peripheral nerves [Rushton, ] but g ‐ratio values have been reported to be larger in the CNS in experimental data [Guy et al, ; Mason et al, ]. It has been suggested that in the healthy condition axons and their microscopic substructures (e.g., their g ‐ratio) are finely tuned biological devices and that changes of their composition can lead to clinical syndromes [Coggan et al, ]. This makes the g ‐ratio a functionally important property of axons and as such a relevant marker in patients and healthy volunteers alike.…”
Section: Introductionmentioning
confidence: 99%
“…A fiber with a g ‐ratio around 0.6 has been theoretically shown to provide maximal speed of conducting neural signals in peripheral nerves [Rushton, ] but g ‐ratio values have been reported to be larger in the CNS in experimental data [Guy et al, ; Mason et al, ]. It has been suggested that in the healthy condition axons and their microscopic substructures (e.g., their g ‐ratio) are finely tuned biological devices and that changes of their composition can lead to clinical syndromes [Coggan et al, ]. This makes the g ‐ratio a functionally important property of axons and as such a relevant marker in patients and healthy volunteers alike.…”
Section: Introductionmentioning
confidence: 99%
“…Coggan in his study showed tongue somatosensory evoked potentials are an efficient method for evaluating the afferent trigeminal nerve in MS patients. He claimed it is more sensitive than MRI to detect early damage [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Signal transmission along different axonal fibres can be regulated and synchronised by varying the degree of myelination, and therefore the g-ratio, to optimize cognitive function, sensory integration and motor skills ( Fields, 2015 ). As the central nervous system appears to communicate at physical limits to constrain metabolic demands ( Salami et al, 2003 ; Hartline and Colman, 2007 ; Coggan et al, 2015 ), small deviations from the optimal g-ratio value (0.6−0.8, ( Rushton, 1951 ; Chomiak and Hu, 2009 )) may have strong functional impact.
Fig.
…”
Section: Introductionmentioning
confidence: 99%